Retention and Academic Success of First-Year Student-Athletes and Intramural Sports Participants. Issue 1 (April 2019) - McElveen, Michael; Ibele, Kelly
The purpose of this investigation was to compare the relationship of intramural sports and Division III athletic participation to retention and academic success in first-year college students. A first-year student cohort ( n = 568) was grouped into four categories: no participation, student-athlete, intramural participant, and participant in both. There was no statistically significant difference in academic success among the participant groups, F (6, 1084) = .626, p = .710. Both the student-athlete and intramural participant groups were retained at a higher rate than the no participation group, 4.65% and 10.48%, respectively. Of the 46 student-athletes who discontinued playing varsity sports, only 17 remained at the institution. This investigation supports that intramural sports and Division III varsity athletic participation does not negatively affect grade point average and credit hours earned in first-year students, while demonstrating a positive relationship with retention. The results also highlight the need for intentional intervention and research related to the disengaged student-athlete.